2021
DOI: 10.1038/s41377-021-00542-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo flow cytometry reveals a circadian rhythm of circulating tumor cells

Abstract: Circulating tumor cells (CTCs) is an established biomarker of cancer metastasis. The circulation dynamics of CTCs are important for understanding the mechanisms underlying tumor cell dissemination. Although studies have revealed that the circadian rhythm may disrupt the growth of tumors, it is generally unclear whether the circadian rhythm controls the release of CTCs. In clinical examinations, the current in vitro methods for detecting CTCs in blood samples are based on a fundamental assumption that CTC count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 61 publications
(63 reference statements)
0
44
0
Order By: Relevance
“…Advanced GU cancers have poor outcomes and high mortality rates, making the development of therapeutic targets a time-sensitive task ( 142 ). A pioneering research study of circulating tumor cells, which are biomarkers of metastasis, has shown to follow specific circadian rhythmicity in animal models of PCa ( 143 ). By targeting PCa treatment to coincide when circulating tumor cells are at their highest concentration in the bloodstream, clinicians may be able to produce robust patient responses to treatment ( 143 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced GU cancers have poor outcomes and high mortality rates, making the development of therapeutic targets a time-sensitive task ( 142 ). A pioneering research study of circulating tumor cells, which are biomarkers of metastasis, has shown to follow specific circadian rhythmicity in animal models of PCa ( 143 ). By targeting PCa treatment to coincide when circulating tumor cells are at their highest concentration in the bloodstream, clinicians may be able to produce robust patient responses to treatment ( 143 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the analytical model developed in this work can be further applied to predict the cell transiting speed for other cell types with different ranges of physical parameters (e.g., diameter and elasticity) and microchannel configurations (e.g., width and height); and therefore this model can guide the design of microchannels for a specific cell type flowing within a target range of the transiting speed for any further biosensing applications, including viscoelasticity measurements [32] and characterization of fluorescence signals from the in vivo flow cytometry [33] for CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one might expect tumors to desynchronize from an individual's circadian rhythm, considering that malignant cells often have dysfunctional clock gene expressions. A recent prostate cancer model demonstrated tumor behavior that was in phase with the circadian rhythm of host mice, but desynchronization into non-24-h rhythms has been documented in a variety of human cancers [155,156]. Future research might consider to what extent tumors resynchronize in response to host entrainment.…”
Section: Future Directionsmentioning
confidence: 99%